KUALITAS FISIK GARLIC OIL DAN POTENSINYA SEBAGAI ANTIMIKROBA STREPTOCOCCUS AGALACTIAE PENYEBAB MASTITIS PADA SAPI PERAH - Lili Zalizar (Jurnal Gamma, 2012)
KUALITAS FISIK GARLIC OIL DAN POTENSINYA SEBAGAIANTIMIKROBA STREPTOCOCCUS AGALACTIAEPENYEBAB MASTITIS PADA SAPI PERAHLili ZalizarStaf Pengajar Jurusan Produksi Ternak, Fakultas Pertanian PeternakanUniversitas Muhammadiyah Malangemail: 1) lilizalizarthahir@yahoo.comABSTRACTThe research aims to determine the physical quality of garlic oil preparation with a carrier oil type and duration of the different savings and to determine potential as an antibacterial preparation have been made in the Livestock Department of Animal Health Laboratory Muhammadiyah University of Malang. This experiment uses two types of treatment are the type of carrier oil and storage time. The treatment consists of the type first carrier oil of garlic in olive oil (A1) of garlic in coconut oil; third treatment (A2) garlic in oil palm. The treatment consists of a long storage time 1 month storage (B1), storage for 2 months (B2) and storage for 3 months (B3). All treatment was repeated 3 (three) times. Variable measured in this study is the physical quality include odor, color, consistency, turbidity and microbiological quality: Minimum Inhibitory concentration (MIC) and Kill Minimum Concentration (KBM) against the test microorganisms S.agalactiae . Concentrations of garlic oil preparation is checked against the MIC and KBM from start 1.5%, 3.12%, 6.25%, 12.5%, 25%, 50% and 100%. From the results of this study concluded that the stock garlic oil with coconut oil carriers have better physical properties and durable storage. Garlic preparations with a carrier oil coconut oil have the power to kill the inhibition and higher against bacteria Sterptococcus agalactiae, which is one of the bacteria that cause mastitis in dairy cows.Key word : garlic oil, physical properties, antibacterial